Encyclopedia of Inorganic and Bioinorganic Chemistry 2016
DOI: 10.1002/9781119951438.eibc2458
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mixed Metal Oxides in Heterogeneous Catalysis

Abstract: In this article, we include numerous types of mixed metal oxides (MMOs) including their properties and catalytic applications for several types of reactions, focusing on their active sites (acidic and basic). Owing to the acid–base and redox properties of MMOs, they establish a largest family of catalysts in heterogeneous catalysis. Generally, in most of the examples, MMOs have superior properties in terms of acidic or basic sites and surface area than single oxide. In addition, some examples of mixed metal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Mixed metal oxide (MMO) is one of the most important photocatalysts, with features that differ from ordinary oxides in circumstances such as acid-base, redox, and surface area. These have been widely explored for several catalytic applications due to their excellent chemical-thermal stability compared to single oxides [70][71][72].…”
Section: Mixed-metal-oxide-based Photocatalystmentioning
confidence: 99%
“…Mixed metal oxide (MMO) is one of the most important photocatalysts, with features that differ from ordinary oxides in circumstances such as acid-base, redox, and surface area. These have been widely explored for several catalytic applications due to their excellent chemical-thermal stability compared to single oxides [70][71][72].…”
Section: Mixed-metal-oxide-based Photocatalystmentioning
confidence: 99%
“…The use of oxide systems for the organization of catalytic processes primarily involves an increase in the specific surface area of the carrier. Another important parameter is the need for maximum concentration of catalytically active centers with high donor-acceptor capacity [20].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In recent years, mixed-metal oxides have been widely used for the catalytic oxidation of soot, CO, and volatile organic compounds due to their comparable catalytic activity and high thermal and chemical stabilities compared to single-component oxides [ 7 , 8 ]. Kuwahara et al reported that the doping of Fe into Mn 2 O 3 significantly increased the concentration of adsorbed oxygen, resulting in a decrease in the T 50 of the MnO x catalyst from 339 °C to 328 °C for soot oxidation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%